PERAN UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM MENANGGULANGI MASALAH DRUG TRAFFICKING DI PAKISTAN 2016-2020 - Wardani, Indah Surya; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Security issues in international studies have expanded from the initial focus on the military to non-traditional security issues. One of the non-traditional issues that have major impact on the country and global society is drug trafficking. Pakistan has become one of the locations for widespread drug trafficking because it is located in the Golden Crescent region which is one of the world's drug-producing locations. The drug problem affects the social, economic and health of the Pakistani population. As an effort to overcome these problems, Pakistan is under the supervision of the United Nations Office on Drugs and Crime (UNODC) which handles transnational crimes such as drug trafficking. This study used the perspective of Pluralism with the level of analysis of country groups. The theory used in this research is the International Organization Theory. The qualitative method in this study used secondary data sourced from websites, official reports and documents, journals, books and news. This study showed that the cooperation carried out by the United Nations Office on Drugs and Crime (UNODC) in Pakistan taken place because Pakistan cannot handle the problem of drug trafficking alone. The role played by the UNODC organization in dealing with the problem of drug trafficking in Pakistan is as an initiator: initiating Country Program II, initiating cooperation with Japan and Denmark, and as a facilitator: building security infrastructure, providing aid tools for law enforcement and facilitating Triangular Initiative cooperation.Keywords: United Nations Office on Drugs and Crime, Drug Trafficking, Drugs, International Organisation